Systemic Amyloidosis: A Rare Presentation of Mesenteric Angina - Christopher N Andrews; Jack N Amar; Malcolm MM Hayes; Robert A Enns (Canadian Journal of Gastroenterology)
A 64-year-old man presented with an eight-month history of increasing postprandial epigastric pain and a 15 kg weight loss. Computed tomography of the abdomen, panendoscopy and mesenteric angiography failed to explain the cause of the patient's mesenteric angina. Systemic amyloidosis involving intestinal small vasculature without larger arterial involvement was diagnosed at autopsy after the patient died of an asystolic cardiac arrest. Mesenteric angina without evidence of ischemic enteritis or pseudo-obstruction is a rare manifestation of amyloidosis.